Application of an optimized electrochemical sensor for monitoring astaxanthin antioxidant properties against lipoperoxidation1. (27th August 2015) - Penu, Ramona; Litescu, Simona Carmen; Eremia, Sandra A. V.; Vasilescu, Ioana; Radu, Gabriel-Lucian; Giardi, Maria Teresa; Pezzotti, Gianni; Rea, Giuseppina
<x xml:space="preserve">Abstract</x> This paper reports the first renewable electrochemical sensor that is able to provide reliable in vitro information on carotenoid antioxidant properties by mimicking their natural position and orientation in the cellular membrane.